A Systematic Search and Mapping Review of Studies on Intracerebral Microdialysis of Amino Acids, and Systematized Review of Studies on Circadian Rhythms. (9th October 2018) - Leenaars, Cathalijn H. C.; Freymann, Jennifer; Jakobs, Koen; Menon, Julia M. L.; Van Ee, Thomas J.; Elzinga, Janneke; Kempkes, Rosalie W. M.; Zoer, Bea; Drinkenburg, Pim W. H. I. M.
Background: Microdialysis can be used to measure amino acids in the extracellular space in vivo, based on the principle of diffusion. Variations in experimental set-up result in variations in baseline levels of the compounds measured. Variations may also be due to circadian rhythms. Method: We systematically searched and mapped the literature on all studies reporting baseline microdialysis measurements of histamine and the amino acids asparagine, aspartate, GABA, glutamate, glutamine, glycine, proline and taurine. We fully reviewed the studies describing circadian rhythms for histamine and the selected amino acids. Results: We retrieved 2331 papers describing baseline measurements of one or more of the compounds of interest. We provide a numerical summary and lists of the publications by compound. We retrieved 11 references describing studies on the circadian rhythms of the compounds of interest. Aspartate, glutamate and histamine are generally higher during the dark than during the light phase in nocturnal rodents. For glutamine, no rhythmicity was observed. For GABA, the results were too inconsistent to generalise. For asparagine, glycine, proline and taurine, insufficient data are available. Conclusion: The literature on intracerebral microdialysis measurements of the amino acids is vast, but certain primary studies are still warranted. Future systematic reviews on the individual compounds can shed light on the effects of experimental variations on baseline concentrations.